Oral vaccination with a rough attenuated mutant of S. Infantis increases post-wean weight gain and prevents clinical signs of salmonellosis in S. Typhimurium challenged pigs - Foster, Neil; Richards, Luke; Higgins, John; Kanellos, Theo; Barrow, Paul (Elsevier, 2016)
We show that oral inoculation of 14 day old conventional piglets with a rough attenuated Salmonella enterica serovar Infantis 1326/28Фr (serogroup C1), 24 h prior to oral challenge with S. enterica serovar Typhimurium 4/74 (serogroup B), resulted in significant weight gain (~ 10%) measured at 14 days post-weaning (38 days of age). Two days after challenge the S. Typhimurium induced stunting and, in some cases loss, of villi but this was prevented by pre-inoculation with the S. Infantis strain. The clinical signs of disease associated with S. Typhimurium 4/74 challenge and faecal shedding were also significantly (P < 0.05) reduced by pre-inoculation with the S. Infantis mutant. Pre-inoculation of pigs with the S. Infantis mutant also increased weight gain in pigs challenged with pathogenic Escherichia coli. However, Mycobacterium bovis BCG, an unrelated intracellular bacterium, did not protect against challenge with S. Typhimurium 4/74.